Pengaruh Latihan Skipping Terhadap Daya Tahan Kardiovaskular (Vo2max) dan Daya Ledak Otot Tungkai Atlet Taekwondo Mapan Club Surabaya - Danubisma, Ivanov; Dewi, Ratna Candra (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2023)
The aim of this study is to determine the effect of skipping exercises on VO2Max and leg muscle explosiveness in athletes from the Taekwondo Mapan Club Surabaya. Method: This study utilized the One- Group Pretest-Posttest Design. The sample consisted of athletes from the Taekwondo Mapan Club Surabaya. The variables in this study were VO2Max, leg muscle explosiveness, and skipping exercises. In this study, skipping exercises were conducted for 6 weeks, with 3 sessions per week. Skipping exercises were performed with a frequency of 20 repetitions, which increased by 5 repetitions per week, repeated in 3 sets with a rest period of 3 minutes. Data were analyzed using the Paired Sample t-test with a significance level of < 0.005. The results of this study showed that there was an effect of skipping exercises on VO2Max and leg muscle explosiveness in athletes from the Taekwondo Mapan Club Surabaya. Keywords: leg muscle explosiveness, skipping, VO2Max